Development of sciencematerials -based science, technology,engineering, and mathematics (STEM) for improving critical thinking skills of elementary school students - L Yulianti; H K Surtikanti (Pascasarjana Universitas Pendidikan Indonesia, 2018)
Indonesian education in the era of the fourth industrial revolution should be able to produce generations have the critical thinking skill and ready to compete with technological advances in the future. Currently research on the development of teaching materials based on Science, Technology, Engineering, and Mathematics (STEM) is needed to change paradigm of education from partial to holistic. This research is a preliminary study to develop STEM-based science materials to improve students' critical thinking skills. The type of research conducted is Research and Development (RnD) with the development model of Borg and Gall. This study realized the first and second steps of the seven steps to be taken. Preliminary study was conducted in 5 schools involving 50 elementary school teachers and 100 students. The results of this study indicate that science and math learning is a key development of technology today. Students and teachers need teaching materials that combine science, technology, engineering and math as a new breakthrough in learning. With engineering-based learning, students are expected to think more critically critical.